PREVALENCE OF HELMINTH EGGS IN CAT FECES CONTAMINATING PUBLIC AREAS IN SURABAYA - Wahyudi, Nurul Tri; Suwanti, Lucia Tri; Kusnoto, Kusnoto; Mumpuni, Sri; Yudaniayanti, Ira Sari; Mafruchati, Maslichah (Institute of Topical Disease Universitas Airlangga, 2017)
Helminthiasis can be transmitted from animals to humans (zoonosis). Helminthiasis can cause cutaneus larva migrants, visceral larva migrant, and occular larva migrants. Cats are the most easily animals can found in public areas. cats have a habit of defecating in areas, such as dusty soil, gardens, sand pits, trash cans, and even children's playgrounds. Proximity of human life with a stray cats is one of the potential that can helminthiasis transmited to humans. The purpose of this study was to assess the prevalence of helminth eggs (species and number) observed in cat feces contaminating public areas in Surabaya. Cross-sectional study have been observations cats existense and examination laboratory of 180 cat fecal samples were collected from canteens, markets, villages, schools, and parks across 5 areas in Surabaya. Helminth eggs present in fecal samples were identified using direct smear, sedimentation, and flotation methodes, and quantified as fecal egg count (eggs per gram of feces) with McMasster method. The test results positive for helminthiasis if found one or more types of helminth eggs in fecal samples. Helminth eggs were present in 68 (37.8%) of the 180 cat fecal samples contaminating public areas in Surabaya. Results of chi-squared analysis confirmed the prevalence of helminth eggs in cat fecal samples contaminating canteen, markets, villages, schools, and parks in Surabaya (p > 0.05). The species causing environmental contamination included Ancylostoma sp. eggs, Toxocara cati eggs, and Toxascaris leonina eggs. The level of environmental contamination, as assessed using ANOVA, was 200 eggs per gram of feces.